2019
DOI: 10.1111/cch.12639
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and understanding of the Ages & Stages Questionnaires®, Third Edition, as part of the Healthy Child Programme 2‐year health and development review in England: Parent and professional perspectives

Abstract: BackgroundThe Healthy Child Programme is the universal public health system in England to assess and monitor child health from 0 to 19. Following a review of measures for closer monitoring at age 2 years, the Department of Health for England implemented the Ages & Stages Questionnaires®, Third Edition (ASQ‐3™; Hereon, ASQ‐3).AimThe aim of this study was to evaluate the acceptability and understanding of the ASQ‐3 in England by health professionals and parents.MethodA mixed‐methods approach was used. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Summing up total scores for each domain yields the total score (out of 60). Higher scores are indicative of healthier outcomes (Kendall et al, 2019). The ASQ-3 is found to have adequate internal consistency reliability (between 0.82 and 0.88), sensitivity of 86% and a specificity of 85% (Mackrides & Ryherd, 2011).…”
Section: Pre-and Post-outcome Measuresmentioning
confidence: 99%
“…Summing up total scores for each domain yields the total score (out of 60). Higher scores are indicative of healthier outcomes (Kendall et al, 2019). The ASQ-3 is found to have adequate internal consistency reliability (between 0.82 and 0.88), sensitivity of 86% and a specificity of 85% (Mackrides & Ryherd, 2011).…”
Section: Pre-and Post-outcome Measuresmentioning
confidence: 99%
“…The Children's Commissioner and (ex)PHE both estimate that 9 out of 10 children receiving a 2-2½ year review also had an ASQ-3 completed but other studies have found significant variability across England in the implementation and reporting of the ASQ-3. [13][14][15] The subuniversal reach of the 2-2½ year review has prompted questions about whether some children are systematically more likely to miss out on a review. In 2020, the Children's Commissioner tried to ascertain if vulnerable children were differentially likely to have a 2-2½ year review than their peers but found that most LAs did not collect the necessary data, concluding: 'There is little evidence that local areas are ensuring that their vulnerable young children are checked'.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“… Delivery of the HCP by health visiting teams and use of ASQ-3 and ELIM in the 2–2½ year review. 15 29–44 …”
Section: Introductionmentioning
confidence: 99%
“…When children fail to perform, parents might overvalue their child’s developmental performance to avoid this perceived failure. The utilization of the ASQ-3 in itself can raise anxiety leading to distortion of the results or at times incomplete filling of the questionnaire ( Kendall et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%